2019
DOI: 10.34172/ajcmi.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Neospora caninum and Toxoplasma gondii Infections in Stray Dogs of Hamadan Suburb, West of Iran, 2018

Abstract: Dogs exposed to zoonotic parasites (e.g., Leishmania spp., Toxoplasma gondii, Toxocara spp., Echinococcus granulosus sensu lato) represent a threat to public health (1). Moreover, some dog-associated pathogens (e.g. Neospora caninum and Taenia spp.) may frequently infect livestock and cause economic losses due to fatality, abortions, and spoilage of meat and other edible tissues (2).Neospora caninum (Apicomplexa: Sarcocystidae) is an intracellular heterogeneous parasite with cosmopolitan distribution (3). Cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
2
2
0
1
Order By: Relevance
“…It seems there was a direct relationship between the history of abortion and the seropositivity rate of T. gondii [ 29 , 57 ]. Moreover, the proportion of abortions and number of aborted fetuses in the last year were in significant correlation with the occurrence of T. gondii , consistently with the findings of Benlakehal et al [ 29 ] and Gharekhani et al [ 58 ], whereas an insignificant association was reported previously [ 34 , 42 , 54 ]. Several studies have used serological methods to identify reproductive losses associated with T. gondii [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…It seems there was a direct relationship between the history of abortion and the seropositivity rate of T. gondii [ 29 , 57 ]. Moreover, the proportion of abortions and number of aborted fetuses in the last year were in significant correlation with the occurrence of T. gondii , consistently with the findings of Benlakehal et al [ 29 ] and Gharekhani et al [ 58 ], whereas an insignificant association was reported previously [ 34 , 42 , 54 ]. Several studies have used serological methods to identify reproductive losses associated with T. gondii [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to published research, the frequency of T. gondii infection among sheep in various regions of Iran ranges from 3.3% to 38.3% (26). Comparing the results of the present study to earlier studies in Iran revealed that the prevalence of our seropositive sheep was similar to other parts (27)(28)(29). Variations in prevalence can be explained by factors such as climate, age, animal breeding conditions, and different parasite detection techniques (30).…”
Section: Discussionsupporting
confidence: 73%
“…Contrariamente en las majadas caprinas esta variable no fue un factor de riesgo, coincidiendo con Utuk y Eski, (2019) y diferenciándose de otros hallazgos que han demostrado que existe una relación entre el aborto y la seropositividad a N. caninum en cabras (Mesquita et al, 2013;Araujo Rodrigues et al, 2020). En el mismo sentido tanto en Irán como en Brasil, Gharekhani et al (2018), Topazio et al (2014) y Varaschin et al (2011 observaron que en las cabras seropositivas el riesgo de padecer abortos era casi de 3 a 4 veces mayor en comparación con cabras y majadas seronegativas.…”
Section: Discussionunclassified